Development of electric vehicle: public perceptionand attitude, the Malaysian approach - Rahman, Mohammed Ataur; Rafia, Afroz; Alam, A. H. M. Zahirul (Inderscience Publisher, 2014)
The rising energy demand has compounded with fuel subsidies and a volatility of oil prices has set the transport sector on an unsustainable course and posed a threat to national energy security in Malaysia. Moreover, it contributes significantly to the green house gas (GHG) emission and causes health as well as environmental damages. Green transport is a feasible transportation technology capable of setting the transportation sector in a sustainable course. The focus of this study is to develop an electric car driven by an electrical motor powered by 84.6 kWh of LiFePO4 battery with an evaporative cooling battery thermal management system (EC-BThMS). The EC-BThMS has been able to keep the battery temperature in the range of 25°C to 40°C. The justification of the introduction of green vehicle was made by the investigation of public preference and attitude towards green transport. The results of the survey indicate that 54% of respondents seriously like to purchase environmental friendly green transport.